2012
DOI: 10.1155/2012/695136
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Temporomandibular Joint on Magnetic Resonance Imaging according to Growth and Development in Schoolchildren

Abstract: The paper explains the alterations of the temporomandibular joint (TMJ) visualized by magnetic resonance imaging (MRI) according to the growth and development of schoolchildren. Appearance and disappearance of a “double contour-like structure” (DCLS) of the mandibular condyle on MRI according to the growth and development of schoolchildren were demonstrated. In addition, possible constituents of DCLS and the significance of detection of DCLS on MRI were also speculated. The relationship between red marrow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The time of alternation of DCLS is close to or coincident with the eruption of upper second molars. Consequently, a statistically significant correlation exists between the timing of the double contour‐like structure's alternation and the emergence of the upper second molars 24–26 . In patients with CUMOL, the second primary molar provides posterior occlusal support until the second molar erupts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time of alternation of DCLS is close to or coincident with the eruption of upper second molars. Consequently, a statistically significant correlation exists between the timing of the double contour‐like structure's alternation and the emergence of the upper second molars 24–26 . In patients with CUMOL, the second primary molar provides posterior occlusal support until the second molar erupts.…”
Section: Discussionmentioning
confidence: 99%
“…Double contour-like structures (DCLS) on the top of the mandibular condyles appeared as high-intensity stripes over a crescent of low-intensity area on intermediate-weighted images, Morimoto et al24 have demonstrated that loose highly vascularised fibrous tissue, proliferation of cartilage cells with immature ossifification of the mandibular condyle and presence of red marrow are the potential features of the DCLS. Regarding the clinical implications of DCLS, alterations in DCLS may be useful criteria for assessing the staging of bone ossification in mandibular condyle, and maturation of the TMJ [24][25][26]. The presence of double contour-like structure indicates condylar growth, while its absence signifies complete growth and osseous maturity.…”
mentioning
confidence: 99%